2015
DOI: 10.3846/13923730.2014.893913
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Model for Double-Skinned Concrete-Filledsteel-Tubular Columns With External Confinement

Abstract: Recent advances in the production of super-fine cement and filler technology has made the production of high-strength concrete (HSC) of 120 MPa practicable in the industry. Nonetheless, the application of such HSC in real construction is still limited. One of the reasons that inhibits the use of HSC is the brittleness, which causes HSC structures to fail explosively if the concrete confinement is not adequate. The traditional method of installing transverse steel as confinement is not feasible in HSC structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The empirical formulas to check the ultimate capacity were suggested. This suggested relation can predict the strength of CFDST and can be useful for structural designers (Dong and Ho, 2015;Ho and Dong, 2014). Further, various studies were conducted on stiffened CFDST columns' behavior under axial concentric and eccentric compressive forces.…”
Section: Introductionmentioning
confidence: 98%
“…The empirical formulas to check the ultimate capacity were suggested. This suggested relation can predict the strength of CFDST and can be useful for structural designers (Dong and Ho, 2015;Ho and Dong, 2014). Further, various studies were conducted on stiffened CFDST columns' behavior under axial concentric and eccentric compressive forces.…”
Section: Introductionmentioning
confidence: 98%
“…The proposed equation was, Np=AfcAc+BfitalicyoAitalicso+CfitalicyiAitalicsi, to estimate the strength of CFDST column subjected to uniaxial loading and is useful for structural designers. Furthermore, Ding and Ho proposed another theoretical model for capacity of double‐skin specimen with external ring confinement as Np=fiAi+foAo+fc+4.1frAitaliccc. 27 For hollow ratio ranging from 0.56 to 0.72, suggested model accurately predicts the strength of ring confined double‐skinned specimen.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the STCC columns provide greater strength and ductility as well as the lower chance of steel tube buckling compared to the CFST columns (Yu et al 2010). STCC columns were first investigated by Tomii et al (1985Tomii et al ( , 1987, and since then, several research results on the STCC columns have been reported by different researchers in the literature (Han et al 2005(Han et al , 2009Zhang et al 2013;Xiao 2005;Dong, Ho 2015;Lee et al 2014).…”
Section: Introductionmentioning
confidence: 99%